Digital radiography : an introduction - Seeram, Euclid (Delmar, Cengage Learning, 2011)
Synopsis: Digital Radiography: An Introduction for Technologists, presents the physical principles and technical description of digital radiography imaging systems and associated technologies. This book functions as both a primary source for introductory digital imaging courses and as a reference for radiologic technologists and other imaging personnel. The book begins by exploring the many digital image acquisition imaging modalities such as computed radiography (CR), flat-panel digital radiography, digital fluoroscopy, and digital mammography systems in detail, followed by an outline of the essential elements of digital image processing. Associated technologies such as picture archiving and communication systems (PACS) and medical imaging informatics (MII) are also outlined. Finally, the book concludes with a description of quality control procedures for digital radiography.